Jet Groutıng Tekniği İle Zemin Islahı - Doğu, Oral (Fen Bilimleri Enstitüsü, 2015)
Bu çalışma, jet grouting tekniğinin tarihsel, teorik ve pratik geçmişini kapsamaktadır. Yöntemin tanımı, gelişimi, uygulama sistemleri ve geometrisi, uygulama parametreleri, tasarım yaklaşımları ve uygulama alanları incelenmiştir. Esas ağırlık verilen konu ise jet grout kolonları ile sıvılaşma potansiyelinin azaltılması ve jet grout kolonlarının dayanım özellikleridir. Sıvılaşma potansiyelinin değerlendirilmesi için, jet grouting yöntemiyle ıslah öncesi ve sonrası ölçülen kayma dalgası hızları yorumlanmıştır. Jet grout kolonların dayanım özellikleri dört saha çalışmasından yola çıkılarak değerlendirilmiştir. İnceleme alanlarının zemin özellikleri ve zemin mühendisliği değerlendirmeleri sunulmuştur. Zeminin ince dane oranı ve Standart Penetrasyon vuruş sayısının jet grout kolonlarının dayanımına etkisi incelenmiştir. Zeminin ince dane oranı, Standart Penetrasyon vuruş sayısı ve kolonların mukavemet özellikleri arasındaki bağıntı ortaya çıkarılmıştır.

In this study covers the historical, theoretical and practical background of jet grouting technique. Its definition, development, execution and methods, treatment geometry, operational parameters, design approaches, application fields are involved in the study. The main emphasize in the thesis is given mitigation of liquefaction potential by jet grouting columns and strength properties of the jet grouting columns. Evaluating of liquefaction potential is explained measurement of shear wave velocity, which is measured before and after the soil stabilisation with jet grouting columns. The strength properties of jet grout columns is investigated by representing four case studies. The subsoil conditions and foundation engineering evaluations of the investigation areas are represented in the case studies. Effect of the fine content of soil and blow number of Standard Penetration Test on jet grout column strength properties are investigated. Relation of the fine content of soil, blow number of Standart Penetration Test and jet grout column strength is exposed.
Soil Stabilisation With Jet Grouting
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2005
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2005
Keywords: Jet grouting; zemin ıslahı; sıvılaşma; sıvılaşma analizleri; kolonların mukavemet özellikleri.; Jet grouting; soil stabilisation; liquefaction; liquefaction analysis; strength properties of columns.